2022
DOI: 10.3390/jcdd9060172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Concurrent Aerobic Plus Resistance Training on Blood Pressure Variability and Blood Pressure Values in Patients with Hypertension and Coronary Artery Disease: Gender-Related Differences

Abstract: The purpose of this study was to compare changes in blood pressure variability (BPV) and blood pressure (BP) values occurring in response to concurrent training (CT) between the two genders. A total of 35 males and 20 women aged 55–80 years, with hypertension and coronary artery disease, were included. They underwent a 12-week CT program. The aerobic component of CT was performed according to the rate of perceived exertion while the intensity of the resistance component was set at 60% of 1 repetition maximum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Concurrent training, including in the same session aerobic and resistance exercises, has proved more effective than continuous aerobic training alone in reducing short-term BPV in hypertensive males [23], but similar studies failed to show any effect on blood pressure variability in women [24,25]. Caminiti et al [9] first demonstrated the effectiveness of concurrent training in reducing short-term BPV in hypertensive women. Interestingly the authors obtained this result by increasing the training intensity regarding the resistance component of the sessions.…”
Section: Exercise and Blood Pressure Variability And Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Concurrent training, including in the same session aerobic and resistance exercises, has proved more effective than continuous aerobic training alone in reducing short-term BPV in hypertensive males [23], but similar studies failed to show any effect on blood pressure variability in women [24,25]. Caminiti et al [9] first demonstrated the effectiveness of concurrent training in reducing short-term BPV in hypertensive women. Interestingly the authors obtained this result by increasing the training intensity regarding the resistance component of the sessions.…”
Section: Exercise and Blood Pressure Variability And Reactivitymentioning
confidence: 99%
“…For example, the intensity and volume of ET needed to optimize cardiovascular benefits in different clinical contexts remain uncertain; similarly, several mechanisms through which ET carries out its cardiovascular effects are still unclear; lastly, in order to develop an increasingly individually tailored ET prescription, further studies that include specific populations underrepresented in previous trials are needed. This Special Issue collects seven original articles and three reviews evaluating the effects of ET in a wide range of clinical conditions: four out of ten papers deal with ET in chronic heart failure (CHF) [3][4][5][6]; two with benefits of ET in subjects with congenital heart disease (CHD) [7,8]; two with blood pressure (BP) responses to acute or long-term exercise [9,10]; one with cardiovascular response to resistance exercise (RE) in elderly [11] and one with clinical consequences of coronavirus disease (COVID-19) in athletes [12].…”
Section: Introductionmentioning
confidence: 99%